An educational methodology for studying culture as an organizing center in entrepreneurship development - Romanenko, Elena V. (2021)
This research is aimed at working out a systemic and holistic approach to entrepreneurship development, regarding the complex interaction of cultural and economic factors. The research objectives include proposing a new economic and cultural paradigm to study entrepreneurship and to substantiate the provision on the endogenous nature of the relationship between culture and business. The research hypothesis implies the assumption that economic culture should be considered as a supporting frame of a single economic reality, and entrepreneurial culture should be regarded as a backbone structure of entrepreneurial behavior models. The research methods are based on the analysis and comparison of the mainstream and alternative theories, within the framework of which ideas about entrepreneurial activity were formed. An alternative methodology was proposed that arose under the influence of the cognitive-cultural turn in the social sciences based on the complementarity of the structural-functional and communicative-semantic approaches. The conceptual meaning of this methodology is to clarify the role of culture as a backbone factor in the development of the entrepreneurial activity. The relevance of the study is determined by the change in the nature and mechanisms of entrepreneurial activities, the growing role of culture in the economy, and the lack of satisfactory theoretical and methodological approaches.